Upaya Meningkatkan Hasil Belajar PAI Siswa Kelas IV Melalui Metode Card Sort di UPTD SDN 03 Limbanang - Teta Nofliza; Salmiwati Salmiwati; Rina Mala Putri (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study was motivated by the low learning outcomes of PAI in class IV, students are also less active in the learning process so that learning becomes not conducive. The limitations of the media used by the teacher and the teacher's teaching method are one of the causes. The application of the card sort method is expected to help students' understanding in PAI subjects of Asmaul Husna Al Wahhab and Al 'Alim. Therefore, researchers are interested in conducting research with the research problem “Can the card sort method improve the learning outcomes of fourth grade PAI students at UPTD SDN 03 Limbanang?”. The type of research used is classroom action research (PTK) which consists of two cycles. The target of this research is class IV students of UPTD SDN03 Limbanang consisting of 11 male students and 9 female students. Based on the results of the study, the average obtained in the pre-cycle was 61 with a percentage of classical completeness of 45%, the average learning outcomes of students in cycle I were 75 with a percentage of classical completeness of 75% while the average learning outcomes of students in cycle II were 82.5 with a percentage of classical completeness of 100%. From the data above, it can be concluded that the application of the card sort method can improve the learning outcomes of PAI class IV students on the material of Asmaul Husna Al 'Al Wahhab and Al 'Alim at UPTD SDN03 Limbanang, Suliki District, Lima Puluh Kota Regency.